Preventing Foodborne Illness: Bacillus cereus - Karuna Kharel; Kiara Bookman; Renee Goodrich Schneider; Rachael Silverberg; Ploy Kurdmongholtham; Bruna Bertoldi; Keith R. Schneider (EDIS)
Bacillus cereus is a Gram-positive, facultative, anaerobic bacterium characterized by large rod-shaped cells and an ability to form heat-resistant endospores. Since this bacterium is commonly widespread in the environment and is often found in soil, it is naturally present in a wide range of food products of both plant and animal origin. B. cereus grows best in a temperature range of 39ºF (4ºC) to 118ºF (48ºC). Optimal growth occurs within the narrower temperature range of 82ºF (28ºC) to 95ºF (35ºC) and a pH range of 4.9 to 9.3 (FDA 2012).